Bioactivities and production of antihypertensive peptides during fermentation of soy milk by lactic cultures. Issue 2 (17th April 2023) - Hati, Subrota; Patel, Nikita; Pipaliya, Rinkal
Abstract : The objective of this study was to evaluate the effect of pH on fermentative characteristics of selected lactic acid bacteria in soy milk, determining α-galactosidase activity and the utilization pattern of sucrose, raffinose and stachyose during fermentation of soymilk and also to evaluate the angiotensin-converting enzyme (ACE) inhibitory and proteolytic activities. In this study, Lactobacillus helveticus MTCC5463 (V3) reduced maximum pH (pH 4.25) in soy milk (pH 6.5), produced highest viable lactic counts, i.e. 13.32 log CFU/ml in soy milk (pH 8.0) during fermentation. Highest acidity was observed in case of V3 (0.75% lactic acid (LA)) in soy milk (pH 6.5) during fermentation. Overall, lactic acid bacteria performed well in natural soy milk (pH 6.5) as compared to soy milks having pH 7.0 and pH 8.0. V3 also showed highest α-galactosidase activity in comparison to other lactic cultures at pH 6.5. Similarly, Lactobacillus rhamnosus MTCC 5945 (NS4) utilized maximum amount of sucrose and stachyose after 24 h of incubation than other cultures at pH 6.5. NS4 ( L. rhamnosus MTCC 5945) culture showed the highest ACE inhibition activity (65.33%) and the highest proteolytic activity (3.264 mg/ml) in soymilk (pH 6.5). The results suggested that the strains (V3 and NS4) could be used for the development of fermented soy milks to reduce complex soy oligosaccharides.